E-Taxation and Fiscal Governance: A Narrative Review of Compliance, Efficiency, and Equity - Anggraeni, Windi Ariesti (Summa : Journal of Accounting and Tax, 2025)
The digitalization of tax systems has emerged as a transformative trend in global fiscal governance, with electronic taxation reshaping compliance, efficiency, and policy design. This narrative review aims to synthesize evidence on how e-taxation influences taxpayer behavior, enhances administrative operations, and contributes to fiscal equity. Literature was collected through Scopus, Web of Science, and Google Scholar using keywords such as digital taxation, e-tax compliance, tax policy innovation, and electronic invoicing. Inclusion criteria focused on peer-reviewed studies between 2010 and 2025, encompassing diverse methodologies including empirical studies, case analyses, and policy reviews. Findings show that digitalization improves taxpayer compliance by reducing administrative burdens, increasing transparency, and curbing tax evasion. Beyond compliance, it also helps integrate SMEs into the formal economy and strengthens the achievement of sustainable development goals. The discussion highlights infrastructure, human resources, and adaptive regulations as key drivers for successful digital taxation. Future research should prioritize longitudinal assessments, distributive equity analyses, and the governance of emerging technologies. Overall, e-taxation represents both a technological and governance innovation with the potential to build more inclusive and resilient fiscal systems worldwide.